The Impact of Macroeconomic Variables on the Financial Growth of Construction Companies in Indonesia: An Analysis with an Error Correction Model (2010.1 – 2021.4) - Raharti, Rini; Kurniawan, Aditya (Universitas Dian Nuswantoro Semarang, 2025)
This aims to analyze the impact of macroeconomic variables, namely economic growth, inflation rate, and labor wages, on the long-term financial growth rate of construction companies in Indonesia in 2010.1 - 2021.4. The research method uses the Error Correction Model - Engle Grager. The stationary data, a root unit test, the first difference, and a cointegration test are carried out to ensure that the model can be continued with the ECM equation. The data used in this study is a secondary time series data published by the BPS. The result of this study is that there is a long-term balance correlation between economic growth, inflation, and labor wages with the financial growth rate of construction companies in Indonesia for the period 2010.1 - 2021.4. The theoretical contribution of this study is the relationship between macroeconomic variables and the financial growth rate of construction companies in Indonesia. The variables of economic growth, inflation rate, and labor wages correlate with the long-term financial growth of construction companies in Indonesia. The novelty of this research lies in an approach that focuses on the specific characteristics of the construction industry in Indonesia, which is different from previous studies that were primarily conducted in developed countries. This study develops an ECM-based analytical model that considers the adjustment mechanism for short-term imbalances and how macroeconomic variables shape the financial stability of construction companies in the long term. Practically, the results of this study provide policy recommendations for the government and construction industry players in anticipating the impact of macroeconomic variables on the company's financial stability.